Posteromedial Release versus Ponseti Treatment of Congenital Idiopathic Clubfoot: A Long-Term Retrospective Follow-Up Study into Adolescence - Corbu A; Cosma DI; Vasilescu DE; Cristea S (Dove Medical Press, 2020)
Andrei Corbu,1,2 Dan Ionut Cosma,1,3 Dana Elena Vasilescu,3 Stefan Cristea2 1Department of Orthopedics and Traumatology, Clinical Rehabilitation Hospital Cluj-Napoca, Cluj, Romania; 2Department of Orthopedics and Traumatology, University of Medicine and Pharmacy Carol Davila, Bucharest, Romania; 3Department of Orthopedics-Traumatology and Pediatric Orthopedics, University of Medicine and Pharmacy Iuliu Hatieganu, Cluj-Napoca, Cluj, RomaniaCorrespondence: Andrei Corbu Email corbuandrei@gmail.comPurpose: Although many short-term studies have shown the superiority of Ponseti treatment to surgical treatment, studies with long-term follow-up of patients into adolescence are lacking. The aim of this study was to compare the morphological, functional and radiological results of the two methods into and during adolescent age, when both soft tissue and bony procedures can be performed to correct residual deformities.Patients and Methods: We retrospectively evaluated two groups of patients diagnosed with congenital idiopathic clubfoot and treated with either the Ponseti method (34 clubfeet) and surgery in the form of posteromedial release (31 clubfeet). All included clubfeet were clinically fully corrected after initial treatment and final plaster removal. Evaluation was performed with the International Clubfoot Study Group (ICFSG) score.Results: The age at follow-up was 12.8± 1.6 years in the Ponseti group and 13.5± 1.7 years in the surgical group. Excellent or good results were obtained in 26 feet (76%) of the Ponseti group and in 14 feet (45%) in the surgical group. The Ponseti treatment was significantly superior to posteromedial release in terms of the final score (10.58± 6.49 versus 17.26± 8.83, p< 0.001), functional score (p< 0.001) and radiological score (p< 0.001). Residual deformities were clinically present in both groups but were less frequent and less severe in Ponseti-treated patients. Flat-top talus was found to be present in both groups, but the Ponseti method was more protective than surgical treatment against this outcome (relative risk=0.494, p=0.002). The overall foot and ankle mobility was significantly better in the Ponseti group (p< 0.001).Conclusion: The Ponseti method was superior to surgery for treatment of clubfoot and achieved better long-term morphological, functional and radiological results. It preserves better mobility of the foot and ankle, and results in less frequent and less severe residual deformities than surgical treatment.Keywords: residual deformities, relapse, ICFSG score, adductus, calcaneocuboid, flat-top talus